Nicotine induces resistance to erlotinib via cross-talk between α 1 nAChR and EGFR in the non-small cell lung cancer xenograft model. Issue 1 (April 2015) - Li, Heyan; Wang, Shuo; Takayama, Koichi; Harada, Taishi; Okamoto, Isamu; Iwama, Eiji; Fujii, Akiko; Ota, Keiichi; Hidaka, Noriko; Kawano, Yuko; Nakanishi, Yoichi
Highlights: Nicotine affects EGFR/AKT/ERK pathways in NSCLCs. Nicotine promotes tumor growth and induces erlotinib-resistance in the PC9 model. Chronic nicotine exposure causes more significant erlotinib-resistance in vivo . Cross-talk between α 1 nAChR and EGFR is associated with EGFR-TKI resistance. Abstract: Objectives: Given our previously published study, α 1 nicotinic acetylcholine receptor (nAChR) plays an essential role in nicotine-induced cell signaling and nicotine-induced resistance to epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) in non-small cell lung cancer (NSCLC) PC9 cells. The aim of this study was to investigate the potential mechanism between nAChR and EGFR for nicotine-induced resistance to EGFR-TKI erlotinib in the NSCLC xenograft model. Materials and methods: We identified the role of nicotine to EGFR/AKT/ERK pathways and to erlotinib-resistance in NSCLC PC9 and HCC827 cells by MTS assay and western blot. Then, we established the PC9 xenograft model with nicotine exposure and treated mice with erlotinib combined with vehicle or nicotine. Results: We confirmed the effects of nicotine on EGFR/AKT/ERK pathways and determined nicotine's potential in preventing from the effect of erlotinib on NSCLC cells. Then, we showed that nicotine exposures can promote tumor growth and induce resistance to erlotinib in the PC9 xenograft model. Our results also indicated that chronic oral administration of nicotine can cause more significant erlotinib-resistance compared with acute i.v. injection of nicotine through activating α 1 nAChR and EGFR pathways. Conclusions: These results suggest that nicotine contributes to the progression and erlotinib-resistance of the NSCLC xenograft model via the cooperation between nAChR and EGFR.